Nonrelativistic dynamics of the charged particles at cyclotron resonances - Buts, V.A.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2008)
It is shown that transition to the chaotic dynamics of the charged particles at cyclotron resonances can take place on an unusual scenario - not through overlapping of nonlinear resonances, but through qualitative periodic tuning of topology of phase space. It is shown that such scenario can be realized at excitation of low-frequency oscillations by dense flows of the charged particles in the strong magnetic field. Показано, що перехід до хаотичної динаміки заряджених частинок при циклотронних резонансах може відбуватися за незвичайним сценарієм - не через перекриття нелінійних резонансів, а через якісну періодичну перебудову топології фазового простору. Показано, що такий сценарій може реалізуватися при збудженні низькочастотних коливань щільними потоками заряджених частинок в сильному магнітному полі. Показано, что переход к хаотической динамике заряженных частиц при циклотронных резонансах может происходить по необычному сценарию - не через перекрытие нелинейных резонансов, а через качественную периодическую перестройку топологии фазового пространства. Показано, что такой сценарий может реализоваться при возбуждении низкочастотных колебаний плотными потоками заряженных частиц в сильном магнитном поле.